1999
DOI: 10.1136/jnnp.66.4.431
|View full text |Cite
|
Sign up to set email alerts
|

Influence of clinical and demographic variables on quality of life in patients with Parkinson's disease

Abstract: Objectives-To identify the clinical and demographic factors that are associated with a poor quality of life in patients with Parkinson's disease. Methods-233 of a total of 245 patients identified in a community based study in a Norwegian county participated in the study. Quality of life was measured by the Nottingham Health Profile (NHP). The results were compared with those in 100 healthy elderly people. Clinical and demographic variables were determined during a semistructured interview and by clinical exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

33
192
4
12

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 305 publications
(241 citation statements)
references
References 26 publications
33
192
4
12
Order By: Relevance
“…[26][27][28][29] Additionally, sleep disorders have been shown to substantially impact healthrelated quality of life in patients with PD. 30 Few studies have assessed possible relationships between any given sleep disorder and different NMS in PD population. Those studies that did question this relationship primarily assessed RBD, which has been demonstrated to be associated with hallucinations, [31][32][33] cognitive impairment, 34,35 psychiatric comorbidity, 36 increased falls, 36,37 poor emotional functioning, and lower quality of life.…”
mentioning
confidence: 99%
“…[26][27][28][29] Additionally, sleep disorders have been shown to substantially impact healthrelated quality of life in patients with PD. 30 Few studies have assessed possible relationships between any given sleep disorder and different NMS in PD population. Those studies that did question this relationship primarily assessed RBD, which has been demonstrated to be associated with hallucinations, [31][32][33] cognitive impairment, 34,35 psychiatric comorbidity, 36 increased falls, 36,37 poor emotional functioning, and lower quality of life.…”
mentioning
confidence: 99%
“…Nos últimos anos, a qualidade de vida dos pacientes com DP tem sido considerada de grande importância, e novos estudos e escalas surgiram para melhor análise 24,[34][35][36] . As escalas mais frequentemente utilizadas são a PDQ -39 (Parkinson's Disease Questionaire) e a SF -36 37 .…”
Section: Discussionunclassified
“…However, there is also a growing literature that shows that even beyond motor disability, depression can be a risk factor for reduced HRQL in PD (Karlsen et al 1995;Hobson et al 1999;. Karlsen et al (1999) used the Nottingham Health Profi le (NHP) to determine which clinical features reduce HRQL in PD. A generic quality of life questionnaire, the NHP, measures six dimensions -emotional reactions, energy, pain, physical mobility, sleep, and social isolation (Jenkinson et al 1988).…”
Section: Depression and Health-related Quality Of Lifementioning
confidence: 99%